The use of ChatGPT to improve scientific article productivity of postgraduate students - Muslimin, Ikhwanul (Journal of Educational Management and Instruction (JEMIN), 2023)
The application of Artificial Intelligence (AI) in education is increasingly promising. ChatGPT as an AI-based platform that can answer all questions can be a solution for learners. This article examines the use of ChatGPT in increasing the productivity of scientific articles of Postgraduate Students of IAIN Kediri. This study used a quasi-experimental design, with the experimental group engaging in scientific article writing using ChatGPT and the control group doing it conventionally. The sample of this study was 2nd semester Postgraduate Students of Islamic Education Management Study Program IAIN Kediri. Data were collected through initial and final tests in scientific article writing. Descriptive and inferential statistical analysis was conducted to analyze the data. The results showed that the average score of the experimental group was 82.68 while the control group score was 68.83. Then the N-Gain value data of the experimental group is greater than the control group with the results of 53.30> 23.01. These results explain the significant increase in scientific article productivity in the experimental group compared to the control group. This finding consistently supports the idea that the use of ChatGPT can increase the productivity of scientific articles for students. The implications of the results for scholarly writing practice are also discussed, along with recommendations for further research.